The Influence Of Public Figure Syahrini's Jargon On Digital Slang Innovation And The Evolution Of The National Language On Social Media - Khadeja Gina Alifia (Jurnal Dieksis ID, 2026)
This study is important to understand how public figure Syahrini’s jargon influences digital slang innovation and contributes to the dynamics and evolution of the national language on social media. This study aims to identify and analyze unique language variations, or idiolects, that appear on YouTube channels, with a particular focus on The Princess Syahrini channel, and to explore their impact on digital linguistic trends. In today’s digital era, social media has significantly transformed patterns of verbal interaction, providing spaces where spontaneous speech by public figures serves as a medium of authentic self-expression and a strategic tool for reinforcing personal branding. This study employs a qualitative descriptive approach with the research subject consisting of naturally occurring spoken interactions captured in video recordings, while the unit of analysis is spontaneous speech units produced by participants during social interaction. Data were collected through systematic video observation, followed by manual transcription and analyzed using detailed coding techniques to identify linguistic and interactional patterns. Data validity was ensured through repeated review of the video recordings, careful verification of transcriptions against the audiovisual data, and consistent application of analytical categories to maintain accuracy and reliability of the findings. The analysis revealed twelve consistently used idiolectal jargons, including expressions such as “Cetar membahana” and “Maju kembali cantik”, which function not only as communicative tools but also as effective strategies for projecting a distinctive public persona. These findings demonstrate that celebrity idiolects act as a primary driver of digital slang innovation, influencing how young audiences communicate online and contributing to the development of hybrid language practices. Furthermore, the study highlights that such idiolects play a role in shaping the evolution of the national language in digital contexts, illustrating how individual linguistic creativity in media environments can extend its impact to broader sociolinguistic trends and contemporary communication norms.